Respuesta :

Answer:

The product is 25

Step-by-step explanation:

we know that

The complex number z1 is equal to

z1=(-4-3i)

we know that

To find the complex conjugate of (-4 - 3i) we change the sign of the imaginary part

so

The conjugate is equal to (-4+3i)

therefore

[tex](-4-3i)(-4+3i)=16-9(-1)=25[/tex]

Answer:

[tex](-4-3i) (- 4 + 3i) = 25[/tex]

Step-by-step explanation:

Notice in the graph that z1 has a real component of -4 and an imaginary component of -3.

Then we know that:

[tex]z_1 = -4-3i[/tex]

By definition for an imaginary number of the form [tex]a-bi[/tex] its conjugate will always be the number [tex]a + bi[/tex]

So the conjugate of [tex]z_1[/tex] is:

[tex]-4 + 3i[/tex]

The product of both numbers is:

[tex](-4-3i) (- 4 + 3i) = 16-12i + 12i-9i ^ 2\\\\(-4-3i) (- 4 + 3i) = 16-9 (-1)\\\\(-4-3i) (- 4 + 3i) = 16 + 9\\\\(-4-3i) (- 4 + 3i) = 25[/tex]